THE ROLE OF ARTIFICIAL INTELLIGENCE IN TEACHING ENGLISH LANGUAGE - Imamaliyeva Gulnoza, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the role of artificial intelligence (AI) in teaching English. It discusses how AI technologies provide personalized learning, interactive practice, real-time feedback, and efficient assessment for language learners. The study highlights the advantages  of  AI  in  enhancing  student  engagement,  supporting  teachers,  and improving  learning  outcomes.  Additionally, the  article  examines  how  AI  tools  can promote motivation, encourage autonomous learning, and facilitate access to global English  learning  resources.  While  AI  is  a  powerful  educational  tool,  it  should  be integrated  alongside  human  instruction  to  ensure  a  balanced  and  effective  English learning experience.